EVALUATION OF THE ANTIBACTERIAL ACTIVITY AND THE TOXICITY OF MAGNESIUM OXIDE NANOPARTICLES ON MICE USING THE LD50 TEST - Sultan, Ameer Radhi; Mohammed, Asma Hadi; Al-Kazaz, Fatin Fadhel Mohammed; MousaHassan, Ahmed (International Journal of Psychosocial Rehabilitation, 2020)
In this research, synthesis of MgO nanoparticles by Co-precipitate method. Results showed that MgO nanoparticles with an average grain size (17) nm. Characterization of MgO nanoparticles was done by X- ray diffraction (XRD), Fourier transforms infrared spectroscopy (FTIR), UV–visible ,Transmission Electron Microscopy (TEM) and Scanning and Electron Microscopy (SEM) were made. The antibacterial activity of MgO nanoparticles (NPs) showed higher inhibition of gram negative bacteria (E.coli) compared to gram positive bacteria (S. aureus ) . Thirty-five male albino mice, divided into seven groups based on concentrations prepared from MgO NPs, each group having five mice and administered for 30 days. The calculated of LD50 was 1200 mg/kg bwt. It has been found that there were non-significant in the organ index of all organs compared to control group with the exception of the liver at a concentration of 1200 mg/kg bwt was found significant elevated. No change in the histology of brain, heart and kidneys organs while there was a significant change in the liver histology at the concentration of 1200 mg/kg bwt of MgO NPs. Mild inflammation of the portal vein and necrotic liver was observed.